The world's top business gurus : lessons from leaders such as : Peter Drucker, Michael Porter, Tom Peters, Edward De Bono, Stephen Covey and Warren Buffett. - Wallis, Ian. (Ahemedabad : Jaico Publishing House, 2012)
Lessons from leaders such as: Peter Drucker, Michael Porter, Tom Peters, Edward de bono, Stephen Covey and Warren buffet the world$1 (Bs top business thinkers in one book a must-read for anyone working in or studying business, The world$1 (Bs top business gurus explains simply and clearly The most important elements from the world$1 (Bs most influential leadership and management thinkers. All major gurus, both past and present, are featured, including: Michael Porter, Tom Peters, Warren buffet, Peter Drucker, Michael gerber, Peter Senge, Jim Collins, Ken Blanchard, Charles handy, Richard Koch, John br>Kotter, Ricardo semler, Stephen Covey, Seth Godin and many more. For each of these renowned thought leaders, this book explains their background, the main theories for which they are known, the context for these theories and how they compare with other business thinking. And crucially, the book also looks at how each theory works in practice. With profiles of 28 of the world$1 (Bs top business minds, this book is an essential introduction to business and leadership thinking.s
Keywords: Business; Leadership